Peran Komunikasi Interpersonal dan Representasi Budaya Lokal dalam Menumbuhkan Minat Wisata melalui Film “Agak Laen” - Andika Saputra S; Aqillah Awanissa S; Fellah Dahayu R; Dwiwin Aldikia W; Muhtalifan Rizki A; Arsih Amalia Chandra P; Wiyata Wiyata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Film, as part of the creative industry, plays an important role in tourism promotion by presenting local cultural narratives in an engaging way. This study aims to analyze how the film Agak Laen (2024), which highlights Indonesian local cultural elements, can generate tourism interest through interpersonal communication between characters and authentic cultural representation. Using a qualitative approach with a literature study method, this research finds that the use of regional languages, visual symbols, and social interactions typical of local communities contribute to shaping the audience's perception of a tourist destination. Moreover, the interpersonal dynamics between characters strengthen social solidarity and create emotional attachment with the audience. The findings indicate that film can serve as a strategic medium for destination branding and cultural identity reinforcement.